Investigation of hydraulic characteristics of a downhole jet pump - Panevnyk, D. O. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2021)
The paper considers the possibility of increasing the energy efficiency of downhole ejection systems by twisting the injected flow with inclined guide elements placed in the flow part of a jet pump. Based on the conservation laws for energy, momentum and flow continuity, there was developed a mathematical model of the vortex ejection system in the form of directflow working and helical injected jets, which allowed obtaining the equation of pressure and energy characteristics of a highpressure jet pump. In the case of zero-twist angle of the injected flow, the obtained dependences take the form of classical known equations that characterize the working process of a direct-flow jet pump. In the process of experimental studies of hydraulic characteristics of a high-pressure jet pump for the case of the injected flow twisting, there was obtained an increase in the injection ratio, relative pressure and efficiency of the jet pump to 19.1, 16.9 and 21.3 %, respectively. The error obtained during the experimental verification of the pressure characteristic of the vortex jet pump does not exceed 9.5 %.